2004
DOI: 10.1002/jcb.20230
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cell cycle regulation in primary human uveal melanoma cultures

Abstract: Uveal malignant melanoma is the most frequent primary intraocular tumor in adult humans. The cellular events leading to neoplasic transformation of normal uveal melanocytes are not well known when compared to other cancers. In this study, we investigated the role of G1 and G1/S regulatory proteins of the cell cycle in human uveal melanoma (UM) primary cell cultures, since these proteins are common targets in tumor development. Further, freshly established and characterized tumor cells are a better model for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26]. Some studies have also shown that cyclin D1 is associated with unfavorable outcomes in cutaneous melanomas and is an independent risk factor for the development of metastases [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26]. Some studies have also shown that cyclin D1 is associated with unfavorable outcomes in cutaneous melanomas and is an independent risk factor for the development of metastases [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that an increase in cell size can regulate proliferation and in particular the progression through the G1 phase of the cell cycle [25]. The tumor suppressor phosphatase and tensin homolog (PTEN) plays a critical role in neural precursor proliferation and growth [26].…”
Section: Gaba a Rs Activation Promotes The Cell Cycle Entry In Neonatmentioning
confidence: 99%
“…10 UM-A < 7, UM-A > 7, NM and UM cell lines (UW-1, OCM-1, SP5.6 and 92.1) were cultured in RPMI medium containing 5% inactivated fetal calf serum (FCS), 2 mM glutamine and standard antibiotics at 37°C in 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…The UM-A primary culture, characterized by the presence of hypophosphorylated and unexpectedly inactive antitumoural protein Rb, changed into a phenotypically different cell line after 7 passages. 10 On the basis of extracellular matrix (ECM) invasion assays that showed a low and high degree of metastatic potential in the UM primary cell culture (UM-A < 7) and cell line (UM-A > 7), respectively, we present here the differential proteome analysis of both cultures. The identification of differentially regulated features reveals an increase in the cellular metabolism of the UM-A cell line and, interestingly, a different expression profile of cancer-related proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation